Better than rational: Evolutionary psychology and the invisible hand - Cosmides, Leda; Tooby, John (American Economic Review, 2016)
Several years ago, we attended an interdisciplinary seminar on what were purported to be biases in negotiation behavior. The economists, psychologists, and biologists present were mulling over the data when, suddenly, a prominent economist lit up. Ah, I see,' he said, is either or it's psychological. This formulation stuck in our minds, because it seemed to succinctly give voice to a tacit assumption held by many economists one that we think works to the detriment of economics, by isolating it from the relevant parts of biology, psychology, and the rest of the natural sciences. This assumption is that behavior is the state of nature, requiring no explanation. Explanations that invoke the cognitive processes that actually generate human choices are required only when behavior deviates from this state of nature. In this view, economics is grounded in assumptions of behavior, is theoretically constructed out of what logically follows from assuming behavior, and gains specificity by plugging in a variety of variables that are kept exogenous to economics, such as preferences. Merchants of the ad hoc and exogenous, psychologists are called in only to provide second-order corrections to economic theory, usually by furnishing a catalog of oddities and quirks in human reasoning (e.g., biases and fallacies-many of which are turning out to be experimental artifacts or misinterpretations; see G. Gigerenzer, 1991). And for the many behavioral domains where standards of rationality are unclear or undefined, economics is presently mute. From a broader scientific perspective, this formulation is decidedly odd. Rational behavior is not, in any sense, the state of nature. Not behaving at all is the state of nature in a universe that includes lifeless planets, prebiotic soup, mountains, trees, and tables. All departures from this state of inaction require explanation. Moreover, the behavioral repertoires of various animals differ profoundly from one another, and this must be explained as well: bats cannot speak, and we cannot navigate through echolocation. Humans and other animals reason, decide, and behave by virtue of computational devices embodied in neural tissue. Therefore, a complete causal explanation of any behavior-rational or otherwise-necessarily invokes theories about the architecture of these computational devices. The rationality of a behavior is irrelevant to its cause or explanation. Every economic model entails theories about these computational devices, but they are usually left implicit, buried in the assumptions of the model. At the moment, most economists rely on the implicit (and somewhat vague) theory that these computational devices somehow embody rational decision rules. But developing a more accurate, useful, and well-defined substitute for this black box is now a realistic goal. Results from the newly emerging field of evolutionary psychology suggest that (i) explicit, well-specified models of the human mind can significantly enhance the scope and specificity of economic theory, and (ii) explicit theories of the structure of the human mind can be made endogenous to economic models in a way that preserves and expands their elegance, parsimony, and explanatory power. *Department of Psychology, University of California, Santa Barbara, CA 93106, and Department of Anthropology, University of California, Santa Barbara, CA 93106, respectively. For enlightening discussions, we warmly thank Gerd Gigerenzer, Robert Nozick, and Paul Romer. For financial support, we are grateful to the McDonell Foundation and NSF Grant No. BNS9157-449 to Tooby.